Localization and characterization of annealing‐induced shunts in Ni‐plated monocrystalline silicon solar cells. Issue 5 (12th February 2014) - Büchler, Andreas; Kluska, Sven; Kasemann, Martin; Breitwieser, Matthias; Kwapil, Wolfram; Hähnel, Angelika; Blumtritt, Horst; Hopman, Sybille; Glatthaar, Markus
Abstract The adhesion of Ni–Cu‐plated contacts requires annealing, which can lead to an electrical degradation of the solar cell. A combination of optical imaging methods and electron microscopical cross‐section analysis was used to investigate the annealing‐induced shunts on monocrystalline solar cells. The results show that Ni spikes cause the lowering of the pseudo fill factor and reveal that these nonlinear shunts show the same behavior as recombination active breakdown sites on multicrystalline silicon solar cells, including radiation of visible light while breakdown. Using reverse biased electroluminescence set‐up the shunts could be localized in top view with µm size lateral resolution. Subsequently, a cross‐section was prepared on a radiative breakdown spot. Advanced electron microscopic investigations reveal defect structures featuring nickel precipitates on the position of the light source. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)